Metastatic basosquamous carcinoma detected by sentinel lymph node biopsy. Issue 8 (3rd June 2013) - Yoshida, Yuichi; Shiomi, Tatsushi; Tahira, Makoto; Yamamoto, Osamu
Abstract: We describe a rare case of basosquamous carcinoma (BSC) in a 69‐year‐old man. He had noticed a pigmented nodule on his left thigh. Dermoscopic examination showed ulceration at the center and non‐typical leaf‐like areas at the periphery. Linear‐irregular vessels were also seen. He underwent tumor excision in addition to sentinel lymph node biopsy (SLNB). Histopathological examination revealed both features of basal cell carcinoma (BCC) and squamous cell carcinoma. The sentinel lymph node was positive for tumor cells. Immunostaining for Ber‐EP4 was focally positive for invasive tumor cells. Although complete inguinal lymphadenectomy had been performed, multiple in‐transit metastases around the primary lesion and left iliac lymph node metastasis developed after the operation. It is considered that BSC has a worse prognosis than BCC with a potential for metastasis. Based on the findings of previously reported cases and our case, SLNB may be applied for certain high‐risk cases including BSC larger than 3 cm in size and careful follow up is recommended for patients with BSC.